Application of energy optimization models to design sustainable energy system: A review - Mondal, Md. Hossain Alam; Mezher, Toufic (2017)
Socio economic development in a society depends on its energy consumption level. Various studies findings on energy indicate that there is a gap between current energy consumption and supply levels. Conventional primary energy reserves will not be able to meet the projected energy demand. So, the present energy system is not sustainable. Alternative resources need to be integrated in the energy supply-mix to meet the expected future energy demand. Fossil-fuel reserve is limited and the use of these fuels has a negative impact on the environment. Holding energy in a secure level and global climate at a safe level requires long-term strategy to integrate renewable energy resources/technologies in energy supply-mix to aim of energy sustainability. A sustainable energy system development approach is fundamental and encompasses various aspects such as energy security objectives, environmental impacts, and economic development. The feasibility of a sustainable energy system can be analyzed applying energy models. Energy models are used to help in energy planning, and to assess alternative national/regional energy policies and integration of clean technologies. This paper presents a design concept of a sustainable energy system and reviews its components. This paper reviews different energy models and presents application of some energy optimization models with consideration of innovated clean technologies in the energy supply-mix in order to achieve a sustainable energy system for a society.